Positive Information of COVID-19 and Anxiety: A Moderated Mediation Model of Risk Perception and Intolerance of Uncertainty - Zhao, Jun; Ye, Baojuan; Ma, Tingting (Frontiers in Psychiatry, 2021)
Although COVID-19 information has been shown to play an important role in anxiety, little is known about the mediating and moderating mechanisms underlying this relationship. In the present study, we examined whether risk perception mediated the relationship between positive information of COVID-19 and anxiety and whether this mediating process was moderated by intolerance of uncertainty. A sample of 3341 college students participated in this study and completed questionnaires regarding positive information of COVID-19, risk perception, intolerance of uncertainty and anxiety. The results indicated that positive information of COVID-19 was significantly and negatively associated with anxiety and that risk perception partially mediated this relationship. Intolerance of uncertainty further moderated the relationship between positive information of COVID-19 and risk perception. Specifically, the relationship between positive information of COVID-19 and risk perception was significant for college students with low intolerance of uncertainty, while it became weaker for those with high intolerance of uncertainty.